Trust Crisis in Public Services: Declining Public Trust in Government Institutions - Ajeng R Indrawati; Andi Asrijal (Socious Journal, 2026)
The decline of public trust in government institutions has emerged as a critical issue affecting the effectiveness of public service delivery. This study aims to analyze the factors contributing to the trust crisis and examine their implications for public services, focusing on institutional performance, service quality, and transparency. A mixed-method explanatory approach was employed, combining quantitative data from structured questionnaires and qualitative insights from in-depth interviews. The data were analyzed using Structural Equation Modeling (SEM-PLS) for quantitative analysis and thematic analysis for qualitative interpretation. The results indicate that institutional performance has a significant direct and indirect effect on public trust, with service quality and transparency acting as important mediating variables. Service quality and transparency also have strong positive effects on trust, highlighting the importance of responsive services and open governance. The findings reveal that poor service delivery and lack of transparency are key drivers of declining trust, while improvements in these areas can enhance public confidence. In conclusion, restoring public trust requires an integrated approach that strengthens institutional performance, improves service quality, and enhances transparency. These efforts are essential to ensure effective, accountable, and citizen-centered public service delivery.